220k views
5 votes
2. Describe the steps you would use to solve the equation
3(4y - 7) = 6.

User Obcure
by
4.6k points

2 Answers

3 votes
Distribution first

3(4y -7)=6

12y -21=6

Next add 21 to both sides to get 12y by itself

12y=27

Divide by 12

You get 2.25

Y=2.25
User Sebagomez
by
4.4k points
2 votes

Answer:

y = 9/4

Explanation:

Step 1: Write equation

3(4y - 7) = 6

Step 2: Solve for y

  1. Distribute 3: 12y - 21 = 6
  2. Add 21 to both sides: 12y = 27
  3. Divide both sides by 12: y = 27/12
  4. Simplify: y = 9/4

Step 3: Check

Plug in y to verify it's a solution.

3(4(9/4) - 7) = 6

3(9 - 7) = 6

3(2) = 6

6 = 6

User StackEdd
by
5.2k points